Prognostic value of magnetic resonance imaging features in low-grade gliomas. Issue 6 (4th June 2019) - Deng, Liang; Shen, Liangfang; Shen, Lin; Zhao, Zhao; Peng, Yingpeng; Liu, Hongjiao; Liu, Haipeng; Zhang, Guangying; Li, Zhanzhan; Li, Kai; Shen, Erdong; Liu, Yuanyuan; et al.
Abstract : Introduction: The treatment strategy for low-grade gliomas (LGGs) is still controversial, and there are no standardized criteria to predict the prognosis of patients with LGGs. Magnetic resonance imaging (MRI) is a routine test for preoperative diagnosis for LGG and can reflect the destructive features for the tumor. In the present study, we aimed to explore the relationship between the MRI features and prognosis in patients with LGG. Methods: Clinical data of 80 patients with pathologically proved LGGs between January 2010 and December 2016 were analyzed retrospectively. MRI features were classified as contrast enhancement pattern (focal enhancement, diffuse enhancement and ring-like enhancement), necrosis and cysts based on the preoperative MR images. Kaplan–Meier method and multivariate analysis were performed on the data by SPSS software to explore the prognostic significance of MRI features. Results: Patients with cystic LGG had a significantly longer 5-year progression-free survival (PFS) than that with no cyst (90.9 ± 8.7 vs 65.7 ± 9.1%, P =0.045). Multivariate analysis further verified cyst as an independent prognosis factor for PFS ( P =0.027, hazard ratio [HR] = 0.084). Additionally, patients with ring-like enhancement exhibited significantly longer 5-year PFS time in the Kaplan–Meier survival curves (100 vs 67.2 ± 7.7%, P =0.049). There was no significant difference in PFS and overall survival (OS) between patients with or without necrosis. Conclusion: Our study suggests that cyst formation and ring-like enhancement on preoperative MR images can be useful to predict a favorable prognosis in patients with LGGs.